Improving Public Speaking Of Pawnshop Employees' Wives Through Optialization Of Product Knowledge And Creative Marketing - Sari, Meutia Dwi Novita; Farma, Junia; Halim, Hendra; Umuri, Khairil (Universitas Syiah Kuala, 2024)
Public speaking is an essential skill in many sectors, including business and financial services. Effective public speaking involves not only speaking ability, but also clarity of information delivery and the ability to motivate the audience. Members of the Pawnshop Employees Wives Association (IIKP) have a strategic role in disseminating information related to pawnshop products and services. However, there is a gap in public speaking skills and product understanding among IIKP members. Therefore, a training program was held that focused on improving public speaking skills, understanding product knowledge, and applying creative marketing strategies. The training used the service learning (SL) method, involved 30 participants with various educational backgrounds, and focused on hands-on practice and application of innovative marketing strategies. The results showed significant improvement in public speaking skills and pawnshop product understanding with higher post-test scores than pre-test. The main challenges encountered included different levels of understanding among participants and limited technological knowledge. The positive impacts of this activity include increased competence of IIKP members in delivering product information with more confidence, as well as the potential to implement more creative and effective marketing strategies. This activity made a significant contribution to women's empowerment and sustainable communication and marketing capacity building